Utilization of insecticide treated nets during pregnancy among postpartum women in Ibadan, Nigeria: a cross-sectional study - Aluko Joel O; Oluwatosin Abimbola O (BMC, 2012)
Abstract Background Pregnant women are susceptible to symptomatic malaria due to invasion of the placenta by plasmodium. Malaria increases the risk of adverse pregnancy outcomes for mothers, the foetuses and newborns. The effective use of Insecticide Treated Nets (ITNs) would be of benefit to these vulnerable women. Previous studies have focused on prenatal-women but this study sought to explore the actual trend of utilization of the proven strategy across all the pregnancy stages among postpartum women in Ibadan. Methods This cross-sectional survey utilized a validated structured questionnaire for data collection. A calculated sample of 335 postpartum women was proportionately recruited from three fee-paying facilities within Ibadan, Nigeria using a simple random sampling technique. These hospitals have high client flow for maternity cases and are known for provision of care under traditional ANC model. The data collected were analyzed using descriptive and inferential statistics by means of Statistical Package of Social Sciences (SPSS) version 15. The level of significance was set at = 0.05. Results The women's age ranged between 18 and 47 years, mean age was 29.4 ± 0.8 years. Various irregularities marked the traditional model of ANC provided at the settings and no exposure to preconception care. Also, 276 (82.4%) had heard of ITNs. Antenatal clinics formed the major source of information. Low utilization and compliance rates were observed. One hundred and twenty-seven (37.9%) of the women had high knowledge of Malaria in Pregnancy (MIP) but only 70 (20.9%) demonstrated positive attitude towards the use of ITNs. Participants' educational status, family types, employment and residential areas significantly influenced ITNs utilization. Conclusions The women knew and learned about ITNs from ANC visits. Majority of the women did not own ITNs because of lack of access to free distribution. The existing traditional model of ANC was marked by irregularities and none of the women was exposed to preconception care. In addition, negative attitude in spite of increased knowledge of MIP was observed among the women. Therefore, evaluation of free distribution of ITNs is recommended. Integration of focused ANC and preconception care are advocated to promote early access to health information.